Penerapan Model Pembelajaran Talking Stick Dengan Diskusi Kelompok Untuk Meningkatkan Motivasi dan Hasil Belajar TIK Siswa Kelas VII C SMP Negeri 1 Sawan Semester Ganjil Tahun Ajaran 2012/2013 - Bagus Suyadnya, I Gusti; Sudirtha, I Gede; Seri Wahyuni, Dessy (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The aims of this class action research are: (1) to know the enhancement of the TIK learning motivation of the student of VII C grade at SMPN 1 Sawan by using talking stick learning model combined with team discusion, (2) to know the TIK learning result of VII C grade at SMPN 1 Sawan by using talking stick learning model combined with team discussion and (3) to know the response of VII C grade at SMPN 1 Sawan in using talking stick learning model combined with team discusion in TIK learning.This research is a class action research consists of two cycles. Each cycle has four steps that are action plan, action implementation, observation and evaluation, and reflection. The research subject is the 35 students of VII C grade at SMP 1 Sawan; while the research object are 1 learning motivation of the student, (2) the result of the learning, 3 the student response in TIK learning by the application of talking stick learning model combined with team discusion. The data collection of the result TIKlearning are collected by test method and observation, and also the data of student response are collected by questionnaire report.The result of this research shows that the studying motivation was elevated from the first cycle to the second one with high category. The studying result was elevated, wich reach 80% for classical accomplishment in the first cycle, and 100% in the second one. Thus, the respond to the talking stick combined with team discussion was positive, with 63,17% average score.